Bone Diseases of the Jaws - Pieter Johannes Slootweg (Hindawi Limited, 2010)
Lesions specific for the jaws and not occurring in any other bones mostly are related to the teeth or to odontogenic tissues. Moreover, the jaws may harbor nonodontogenic bone lesions not seen in any other part of the skeleton. This paper pays attention to the diseases that are specific for the jaws, odontogenic as well as nonodontogenic. Both neoplastic and nonneoplastic entities will be discussed.